A miniaturized horizontally oriented MIMO antenna for 5G and wireless communication systems - Al Gburi, Ahmed Jamal Abdullah; Jemaludin, Nazrin Haziq; Abdulhameed, Muhannad Kaml; Benkhadda, Omaima; Mohammed, Dunya Zeki; Saeidi, Tale; Zakaria, Zahriladha (Intelligent Network and Systems Society, 2025)
The paper introduces a novel compact MIMO antenna specifically engineered for emerging 5G and satellite communication applications. The antenna operates efficiently at 3.5 GHz and 15.6 GHz. Its primary advantage lies in its dual-band capability, achieved through a uniquely designed antenna geometry that enhances inter-element isolation and reduces return loss, all within a highly compact form factor. The proposed antenna features a miniaturized structure with dimensions of 26 × 10 × 1.6 mm³ (0.3λ₀ × 0.12λ₀ × 0.02λ₀), where λ₀ denotes the wavelength at 3.5 GHz—marking a significant improvement over conventional models. The substrate, precisely optimized using CST simulation tools, possesses a low loss tangent of 0.025 and a relative permittivity of 4.3. A prototype of the antenna was fabricated and exhibits omnidirectional radiation characteristics, with peak gain values of –2.6 dBi and 3.04 dBi. Key MIMO performance metrics—including the Envelope Correlation Coefficient (ECC), Mean Effective Gain (MEG), and Diversity Gain (DG)—were evaluated through comprehensive simulations and experimental measurements. A comparative analysis with existing designs highlights the proposed antenna's superior performance and reliability.